2014
DOI: 10.1017/s1041610214002282
|View full text |Cite
|
Sign up to set email alerts
|

The course of neuropsychiatric symptoms in community-dwelling patients with dementia: a systematic review

Abstract: NPS in community-dwelling patients are frequent and persistent. The increasing trends of several NPS in the course of dementia require a preventive approach of professional caretakers. For such an approach, a timely diagnosis and adequate professional support to prevent or diminish these problems is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 52 publications
3
65
0
Order By: Relevance
“…294 BPSD in community-dwelling people with dementia can be severe throughout the course of the condition. 300,301 Longitudinal studies are needed to improve our understanding of the characteristics of people with mild dementia with CB, changes in BPSD over time and what interventions might moderate CB to reduce distress for them, their families and others. Our findings add support to recommendations from studies carried out in other counties for a focused structured assessment of BPSD before deciding on treatment, even in mild dementia, 294 and timely recognition with adequate professional support.…”
Section: Implications For Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…294 BPSD in community-dwelling people with dementia can be severe throughout the course of the condition. 300,301 Longitudinal studies are needed to improve our understanding of the characteristics of people with mild dementia with CB, changes in BPSD over time and what interventions might moderate CB to reduce distress for them, their families and others. Our findings add support to recommendations from studies carried out in other counties for a focused structured assessment of BPSD before deciding on treatment, even in mild dementia, 294 and timely recognition with adequate professional support.…”
Section: Implications For Researchmentioning
confidence: 99%
“…Our findings add support to recommendations from studies carried out in other counties for a focused structured assessment of BPSD before deciding on treatment, even in mild dementia, 294 and timely recognition with adequate professional support. 300 Future applied research studies such as ours will need careful longitudinal evaluation of specialised individualised interventions for home-dwelling people with clinically significant CB, early on following diagnosis of dementia. Given the gaps in knowledge about the management of CB in family settings which have been noted in an independent review of progress of the National Dementia Strategy of 2009 (pp.…”
Section: Implications For Researchmentioning
confidence: 99%
“…A systematic review of studies on the course of NPS in community-dwelling patients with dementia found a cumulative prevalence of any neuropsychiatric symptom between 49% and 95% [3]. Delusions, agitation, aberrant motor behavior and apathy are the most common NPS [3].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of studies on the course of NPS in community-dwelling patients with dementia found a cumulative prevalence of any neuropsychiatric symptom between 49% and 95% [3]. Delusions, agitation, aberrant motor behavior and apathy are the most common NPS [3]. Neuropsychiatric symptoms not only affect the quality of life of the patient [4], but also result in a higher burden of informal caregivers and a lower quality of their lives [4–6].…”
Section: Introductionmentioning
confidence: 99%
“…1 Comorbid neuropsychiatric symptoms (NPS), such as depression, anxiety, apathy, sleep disturbance, agitation, hallucinations and delusions, are extremely common (> 90%) in patients with all NCD subtypes and are usually more prominent in those in advanced stages. 2,3 An underlying medical condition, unmet needs and environmental factors often contribute to the emergence of NPS, which underlines the importance of ruling them out first. 4 Nonpharmacological interventions remain the mainstay of treatment for nonurgent NPS, and guidelines suggest limiting pharmacological interventions to severe, dangerous, or highly distressing symptoms.…”
mentioning
confidence: 99%